# algebra

solve
15t^2+7t=2

1. 👍 0
2. 👎 0
3. 👁 172
1. 15t^2 + 7t -2 = 0

(5t-1)(3t+2) = 0

t = -2/3, 1/5

1. 👍 0
2. 👎 0
2. t =(-b�}�ã(b^2-4ac))/2a

t =(-7�}�ã(7^2-4(15)(-2)))/(2(15))

t=(-7�}�ã(49 +120))/30

t=(-7�}�ã169)/30

t=(-7�}13)/30

t=(-7+13)/30 = 6/30 = 1/5

t=(-7-13)/30 = -(20/30) = -(2/3)

Therefore, t = 1/5 & -(2/3)

1. 👍 0
2. 👎 0

## Similar Questions

1. ### maths!

the formula h=15t-5t^2 gives the height 'h' metres of a ball, 't' seconds after it is thrown up into the air. (i) find the times when the height is 10m (ii) after how long does the bal hit the ground? ive figured out that the

asked by jessica on August 6, 2008
2. ### math

4. What are the coefficients in the polynomial 7x^2 - 4x + 6? A. -7, 4 B. 7, 4, -6 C. 7, -4, 6 D. 7, -4 7. Suppose you earned 6t + 2 dollars on Monday and 9t - 6 dollars on Tuesday. What were the total earnings? Simplify your

asked by zumai on June 1, 2014
3. ### Math

Ms. Sue please help! 7. Suppose you earned 7t – 1 dollars on Monday and 8t + 5 dollars on Tuesday. What were your total earnings? Simplify your answer. (1 point) –t + 4 dollars –t – 6 dollars 15t – 6 dollars 15t + 4

asked by Austin on June 10, 2014
4. ### Polynomials

Suppose you earned 6t + 2 dollars on Monday and 9t – 6 dollars on Tuesday. What were your total earnings? Simplify your answer. (1 point) 15t – 4 15t + 8 –3t – 4 –3t + 8

asked by Anonymous on April 14, 2016
5. ### Math

Im having trouble getting the correct answer to this question. Could someone help out. Monthly sales of a particular personal computer are expected to decline at the following rate of S'(t) computers per month, where t is time in

asked by Anonymous on April 28, 2011
1. ### Pre-Algrebra

3. 2x^2+6x-7x+8-3x^2+1 A. 2x^2+x+9 B. -2x^2-x-9 C. -x^2-x+9 D. x^2+9 4. What are the coefficents in the polynomial 4x^2+3x-3 A. 4,-3,-3 B. 4,3 C. 4,3,3 D. -4,-3 6. (7x^2-x-2)-(6x^3+3) A. 6x^3-+7x^2-x-5 B. -6x^3+7x^2-x+1 C.

2. ### Substitution Method-Plz help

Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get

asked by Svetlana on October 17, 2006
3. ### Algebra

To solve the system of equations, which expression could be substituted for x into the first equation? 3x-5y=14 x+4y=10 a)10-4y b)4y+10 c)(1/4)x+(5/2) d)(-1/4)x+(5/2) I have another problem just like this one so if you could

4. ### Math

7. Suppose you earned 7t – 1 dollars on Monday and 8t + 5 dollars on Tuesday. What were your total earnings? Simplify your answer. (1 point) –t + 4 dollars –t – 6 dollars 15t – 6 dollars 15t + 4 dollars 8. f 2 ∙ f 3 (1

asked by Erika Fernandez on April 26, 2019
5. ### Physics

A particle is moving along a straight line and its position is given by the relation x=( t3-6t2-15t+40)mm. Find:- (a). The time at which velocity is zero. (b). Position & displacement of the particle at that point. (c).

asked by Ram kumar on June 24, 2014
6. ### ALGEBRA 1!PLZ HELP!

Use the Substitution method to solve the system of equations. y - 2x = -5 3y - x = 5 Solve the first equation for y. y = 2x-5 Substitute that for y in the second equation and solve for x. Then use the value of x to substitute back

asked by SANDRO! on November 6, 2006